Analisis Kesalahan Murid Dalam Menyelesaikan Soal Cerita Sudut Bangun Datar Ditinjau Dari Teori Newman Pada Kelas Iii Sd Muhammadiyah I Purworejo - Tanti Setyani; Rintis Rizkia Pangestika; Arum Ratnaningsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to (1) describe the difficulties experienced by third-grade elementary school students in solving word problems on plane geometry angles, (2) analyze the types of students' errors based on Newman's Error Analysis, and (3) identify the factors contributing to these errors. This study employed a descriptive qualitative approach and was conducted at SD Muhammadiyah I Purworejo. Four students were selected as research subjects using purposive sampling based on the results of the written test and the teacher's recommendations. Data were collected through tests, semi-structured interviews, observations, and documentation. The data were analyzed using the stages of data reduction, data display, and conclusion drawing. The findings revealed that the students made errors across the five stages of Newman's Error Analysis, namely reading errors, comprehension errors, transformation errors, process skill errors, and encoding errors. The most dominant errors occurred at the comprehension and encoding stages. The factors contributing to these errors included internal factors, such as limited conceptual understanding, lack of accuracy, and low learning motivation, as well as external factors, including less varied teaching methods and an insufficiently supportive learning environment.